Short-term outcomes after liver resection for malignant and benign disease in the age of ERAS. Issue 2 (February 2016) - Hughes, Michael J.; Chong, Jingli; Harrison, Ewen; Wigmore, Stephen
Abstract: Introduction: Enhanced Recovery After Surgery protocols have been implemented effectively after liver resection and provide benefits in terms of general morbidity rates. In order to optimise peri-operative care protocols and minimise morbidity, further investigation is required to identify factors associated with poor outcome after liver resection. Methods: A retrospective analysis of patients undergoing liver resection and enhanced recovery care between January 2006 and September 2012 was conducted. Data were collected on patient outcome and demographics, operative and pathological details. Univariate and multivariate analyses were performed to determine independent predictors of adverse outcome. Results: 603 patients underwent liver resection during the study period. Morbidity and mortality rates were 34.3% and 1.5% respectively. The only predictor of major morbidity was extended resection (OR 4.079; 95% CI 2.177–7.642). Conclusions: Extended resection is associated with major morbidity. When determining optimum peri-operative care, ERAS protocols must incorporate care components that can mitigate against morbidity associated with extended resection.